The Correlation between Housewives Education Level and Maternal Knowledge about Toddler Health Residing around Landfill - Nurhayati, Heni Aji; Ernawati, E; Rahayu, Sri (Universitas Negeri Jakarta, 2014)
Healthy environment is a basic need for toddlers to have a normal growth and development. Living around a landfill area will greatly impact to their morbidity and mortality rate. Although this condition may not be avoidable, it is assumed that maternal knowledge about toddler health influenced by maternal education level may be an important factor to keep their toddlers healthy. The aim of this study was to know the correlation between housewives education level and maternal knowledge about the toddler health. The study was conducted at RW 04 Kelurahan Kedaung Wetan, Tangerang from May to June 2013. A descriptive correlational with survey technique was applied in this study using 69 housewives with toddler who were selected by simple random sampling. An instrument consists of 27 points of true and false statements was used to obtain data. A strong correlation between housewives education levels and maternal knowledge about toddler health with correlation coefficient of 0.79 resulted from this study. As the conclusion, the housewives education level gave 62.4% contribution to maternal knowledge about toddler health.